Khääsn ‘cauldron’ as a Concept in the Linguoculture of the Kalmyks - Esenova, Galina B.; Esenova, Tamara S. (The New Research of Tuva, 2026)
The article analyzes the concept “khääsn” ‘cauldron’ in Kalmyk linguoculture, focusing on its conceptual, figurative, and axiological dimensions. The linguistic material for the study is drawn from dictionaries of the Kalmyk language, dictionaries of Buryat and Khalkha Mongolian, as well as essays written by Kalmyk respondents in 2025. The study establishes that in Kalmyk the concept “khääsn” ‘cauldron’ has a variety of designations that characterize its functions, size, shape, color, and material. The nominative unit of the concept is the noun “khääsn”, which in contemporary usage has no restrictions in distribution or historical perspective. The conceptual content of the term is that of a universal vessel which simultaneously performs utilitarian, social, and symbolic functions. The figurative component of the concept comprises a large, stable, cast-iron, black, multifunctional item used for preparing milk tea, meat, and araka. Its value component is that of a significant element in the Kalmyk worldview, locally connected with the hearth as the sacred place of the dwelling. In Kalmyk culture, such features of “khääsn” ‘cauldron’ as “full” and “large” are positively evaluated as signs of prosperity, generosity, and the economic competence of the owner. A “empty cauldron” is interpreted as a sign of poverty, lack of hospitality, and social deficiency of the host; the black color of the cauldron can be associated with a negative moral evaluation of a person. The concept “khääsn” functions as a cultural sign that reflects basic Kalmyk ideas about life, food, and social norm. The article concludes that the concept “khääsn” ‘cauldron’ in Kalmyk linguoculture has undergone a long process of reinterpretation, from a household vessel to a “sign of human qualities.” Zoomorphic metaphors, color, quantity, and fullness metaphors, ornithological images, as well as items of nomadic everyday life, which are conceptualized in stable expressions with the participation of verbalizers of the concept, testify to the originality of the figurative thinking of steppe nomads and to the significant place of the concept “khääsn” ‘cauldron’ in the worldview of the Kalmyk people.